2020
DOI: 10.1002/pd.5660
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tobacco chemicals and nicotine on placental development

Abstract: Despite decades of messages warning about the dangers of tobacco use in pregnancy, 10% to 15% of pregnant women continue to smoke. Furthermore, an increased popularity of electronic nicotine delivery systems (ENDS) over the past decade in women of childbearing age raises parallel concerns regarding the effects of vaporized nicotine use in pregnancy. While research using animal models which mimic tobacco smoke and nicotine exposure in pregnancy have largely replicated findings in humans, few studies focus direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…This will allow harmful substances to easily enter the fetus through the placental barrier, causing abnormal development of the fetus (Liu et al, 2018). Cigarette smoke exposure can impair the structure and function of trophoblast cells (Kim et al, 2017; Suter & Aagaard, 2020). Our experiments found that cigarette smoke can increase the expression of pro‐apoptotic factor BAX and the expression of KI67, a cell proliferation marker in placental tissues, suggesting that cigarette smoke can disrupt the placental development process.…”
Section: Discussionmentioning
confidence: 99%
“…This will allow harmful substances to easily enter the fetus through the placental barrier, causing abnormal development of the fetus (Liu et al, 2018). Cigarette smoke exposure can impair the structure and function of trophoblast cells (Kim et al, 2017; Suter & Aagaard, 2020). Our experiments found that cigarette smoke can increase the expression of pro‐apoptotic factor BAX and the expression of KI67, a cell proliferation marker in placental tissues, suggesting that cigarette smoke can disrupt the placental development process.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta collected at birth does not allow measures of DNA methylation changes through pregnancy, but as cord blood, it presents the advantage of being easy to collect after birth [ 107 ], with a high acceptability rate. Placenta also requires few ethical concerns for its use in medical research [ 105 ]. The relationship between DNA methylation in placenta and other tissues will likely vary depending on the target gene, exact location, and timing of sampling.…”
Section: Target Tissues and Proxiesmentioning
confidence: 99%
“…Most studies rely on DNA methylation, which is the best understood and the most cost-effective epigenetic mark to consider in epidemiological studies, and it is conducted on placenta, cord blood, or peripheral children’s blood. Extensive reviews have been published in the last couple of years, including specific reviews on maternal tobacco smoking during pregnancy and epigenetics [ 58 , 104 , 105 ] and more general reviews on smoking and epigenetics [ 106 , 107 , 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of this research excludes pregnant persons, the general risks of exposure to toxicants and organ damage would be expected to apply to pregnant persons who use ENDS as well. Moreover, there may be additional risk to the fetus as a number of these toxicants may pass through the placenta [39].…”
Section: Rationale For Considering Adverse Health Outcomes From Ends Use In Pregnancymentioning
confidence: 99%